Comparative Study on Sybil Attack Detection Schemes - Hamdan, Salam; Al-Qassas, Raad S.; Tedmori, Sara (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Vehicular Ad Hoc Network (VANET) is a wireless network formed between a collection of vehicles connected through wireless connections. VANETs can help increase the passengers comfort, safety, efficiency and convenience by providing them with information about the ongoing road status and other relevant road information. VANETs, similar to other networks, face numerous security threats. One such threat is the Sybil attack, a critical threat that can impair the proper functioning of VANETs. In a Sybil attack, a malicious node illegitimately claims multiple identities and simultaneously exploits these fake identities in order todisturb the functionality of the VANET by disseminating false information. In the presence of a Sybil node, any kind of attack can be launched on the VANET. This paper provides a comprehensive review and comparison of the different techniques that have been proposed in the literature to prevent or reduce the adverse effects of Sybil attacks.